Corruption in The Text and Context of The Qur’an: Maudhu'i's Interpretation Approach - Fikriawan, Suad; Kholiq, Abdul; Parangu, Kaukabilla Alya (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2019)
This article aims to define the meaning of corruption through the text of the Qur’an and contextualize it in the example of the practice of violations committed by several groups of state and regional organizations. The author tries to use the maudhu'i interpretation approach because there are not many studies using this approach and specifically about corruption. Likewise in the Islamic perspective, the text of the Qur'an mentions several terms of corruption such as al-dalw (Al-Baqarah: 188), ghulul (Ali Imran: 161), saraqah (Al-Maidah: 38), and al -suht (Al-Maidah: 42), which in its context experienced an expansion of meaning along with the development of corruption cases that occurred in Indonesia. For example the word al-dalw (Al-Baqarah: 188) implies enriching oneself or others, abuse of authority, and bribery. Ghulul (Ali Imran: 161) implies enriching oneself or others, harming state finances, abuse of authority, embezzlement, gratuity. Then Saraqah (Al-Maidah: 38) implies enriching oneself or another person, harming state finances, abuse of authority, embezzlement. And lastly al-suht (Al-Maidah: 42) implies enriching oneself or others, abuse of authority, bribery Artikel ini bertujuan untuk mendefinisikan arti korupsi melalui teks al-Qur'an dan mengontekstualisasikannya dalam contoh praktik pelanggaran yang dilakukan oleh beberapa kelompok organisasi negara dan regional. Penulis mencoba menggunakan pendekatan interpretasi maudhu'i karena tidak banyak penelitian yang menggunakan pendekatan ini dan khususnya tentang korupsi. Demikian juga dalam perspektif Islam, teks al-Qur'an menyebutkan beberapa istilah korupsi seperti al-dalw (Al-Baqarah: 188), ghulul (Ali Imran: 161), saraqah (Al-Maidah: 38), dan al -suht (Al-Maidah: 42), yang dalam konteksnya mengalami perluasan makna seiring dengan perkembangan kasus korupsi yang terjadi di Indonesia. Misalnya kata al-dalw (Al-Baqarah: 188) menyiratkan memperkaya diri sendiri atau orang lain, penyalahgunaan wewenang, dan penyuapan. Ghulul (Ali Imran: 161) menyiratkan memperkaya diri sendiri atau orang lain, merusak keuangan negara, penyalahgunaan wewenang, penggelapan, gratifikasi. Kemudian Saraqah (Al-Maidah: 38) menyiratkan memperkaya diri sendiri atau orang lain, merugikan keuangan negara, penyalahgunaan wewenang, penggelapan. Dan terakhir al-suht (Al-Maidah: 42) menyiratkan memperkaya diri sendiri atau orang lain, penyalahgunaan wewenang, penyuapan.